Sapodilla Growing in the Florida Home Landscape - Carlos F. Balerdi; Jonathan H. Crane; Ian Maguire (EDIS, 2006)
Revised! HS-1, a 10-page fact sheet by Carlos F. Balerdi, Jonathan H. Crane, and Ian Maguire, provides homeowners with a basic reference for growing sapodilla in the home landscape. Tables include information on selected cultivars for Florida, cultural practices by month, fertilizer program, and nutritional information. This version has also been revised to indicate IFAS' assessment of sapodilla's invasive potential in south and central Florida. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005.